Corrigendum: Self-Compassion and Aggression in College Students - Ferdi W. Djajadisastra (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
After the publication of our article titled “Self-Compassion and Aggression in College Students” (Djajadisastra, 2017), we noted that some parts of the article need to be edited.